Combining thermal imaging and soil water content sensors to assess tree water status in pear trees - Blanco, Victor; Willsea, Noah; Campbell, Thiago; Howe, Orlando; Kalcsits, Lee (Frontiers in Plant Science, 2023)
Volumetric soil water content is commonly used for irrigation management in fruit trees. By integrating direct information on tree water status into measures of soil water content, we can improve detection of water stress and irrigation scheduling. Thermal-based indicators can be an alternative to traditional measurements of midday stem water potential and stomatal conductance for irrigation management of pear trees (Pyrus communis L.). These indicators are easy, quick, and cost-effective. The soil and tree water status of two cultivars of pear trees ‘D’Anjou’ and ‘Bartlett’ submitted to regulated deficit irrigation was measured regularly in a pear orchard in Rock Island, WA (USA) for two seasons, 2021 and 2022. These assessments were compared to the canopy temperature (Tc), the relationship between the canopy and air temperature (Tc-Ta) and the crop water stress index (CWSI). Trees under deficit irrigation had lower midday stem water potential and stomatal conductance but higher Tc, Tc-Ta, and CWSI. Tc was not a robust method to assess tree water status. However, Tc-Ta was greater than 0°C or CWSI was between 0.5 and 0.8 for both cultivars when trees were water limited (midday stem water potential values < -1.2 MPa). Soil water content was an earlier indicator of water limitations than plant indicators but was not as robust as Tc-Ta or CWSI when compared to the midday stem water potential or the stomatal conductance. A multiple regression analysis is proposed for combining both soil water content and thermal-based indices to overcome limitations of individual use of each indicator.